Dampak Transformasi Digital Melalui CRM terhadap Kinerja Layanan dan Kepuasan Pelanggan pada PT. Pupuk Sriwidjaja Palembang - Randy Vemil Prasetiya; Nurmayanti Nurmayanti; Phinton Panglipur (Jurnal Bisnis Inovatif dan Digital, 2026)
This study aims to examine the effect of Digital Customer Relationship Management (CRM) on service performance and customer satisfaction at PT Pupuk Sriwidjaja Palembang. This research is motivated by the importance of implementing digital technology to improve service quality and customer satisfaction in the current digital era. The research employed a quantitative method, with data collected through questionnaires distributed to customers of PT Pupuk Sriwidjaja Palembang. The data analysis techniques included validity testing, reliability testing, classical assumption testing, and linear regression analysis using SPSS software. The variables in this study consisted of Digital CRM as the independent variable, service performance as the intervening variable, and customer satisfaction as the dependent variable. The results indicate that Digital CRM is able to explain 60% of the variance in service performance. Furthermore, 65% of customer satisfaction is influenced by both Digital CRM and service performance. Service performance also acts as an intervening variable in the relationship between Digital CRM and customer satisfaction. Therefore, the effective implementation of Digital CRM can improve service quality, which in turn leads to increased customer satisfaction at PT Pupuk Sriwidjaja Palembang.